Geology and the environment - Bernard W. Pipkin (Thomson Brooks/Cole, 2008)
Pipkin/Trent/Hazlett/Bierman's and GEOLOGY AND THE ENVIRONMENT explores the relationship between humans and the geologic hazards, processes, and resources that surround us. This stellar author team has the most field expertise, and the greatest depth of experience in bringing this field of knowledge to the student, of any in this market. In the 6th edition of this tested market leader the authors have fully integrated coverage of how climate change and global warming impact geologic processes. Both human and non-human-induced climate change topics are discussed in a newly developed chapter called The Earth System and Climate Change. This chapter sets the context for understanding how Man's interaction with the Earth System is a contributor to climate change and global warming. The acclaimed Case Studies feature at the end of chapters now includes 10 cases on climate change and global warming topics. The new edition also introduces a new feature called Questions to Ponder, which further encourages students to think critically about pressing issues of social and environmental importance